ALASAN PENTINGNYA KEHADIRAN TENAGA PEMBIMBING KESEHATAN KERJA DI PUSKESMAS - Muhammad Sultan (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2022)
The cases of work accidents and occupational diseases are still experienced by the informal workers today and have become a crucial challenge in Indonesia. BPJS recorded 61,805 work accident cases from January to March 2022; around 60% of them were the workers in the informal sector. So, the workers in the informal sector experienced more work accidents. The attendance of the health advisors for various tasks and functions needs special attention. Writing a literature review is used as a basis. It reinforces the ideas of researchers in describing the reasons why the attendance of health advisors is required in the health centers legally, economically, socially, culturally, and technically. The present research shows that the essential factors in the existence of health advisors are influenced by moral, economic, legal reasons, the characteristics of the community in the local area, and the challenges of collaboration in implementing occupational health effort posts. In addition, it is imperative to present competent and professional health advisors to prevent work accidents and improve the health status of the informal workers optimally and sustainably. Therefore, the collaboration is needed between local governments through puskesmas, employers, and informal workers to carry out inventories, workload analysis, and fulfillment of occupational health and safety human resources in each health centre